The Effect Of Leadership Style, Village Official Turnover, Village Official Motivation On Village Official Performance Through Work Engagement - Haidi Aryanto; Yusuf Ronny; Fajar Rezeki Ananda Lubis (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to analyze the influence of leadership style, village apparatus turnover, and village apparatus motivation on village apparatus performance through work engagement in Deli Serdang Regency. This study used a quantitative approach with a survey method through questionnaires distributed to 175 village apparatus. Data analysis techniques used were multiple linear regression and mediation analysis to test the direct and indirect effects between variables. The results showed that leadership style and motivation directly influenced village apparatus performance, while turnover had a negative and significant effect on performance. Furthermore, the test results showed that leadership style and motivation positively and significantly influenced work engagement, while turnover had a negative and significant effect on work engagement. Work engagement proved to have a positive and highly significant effect on village apparatus performance. Furthermore, the results of the mediation analysis showed that work engagement acted as an intervening variable, where work engagement partially mediated the effect of leadership style on performance and fully mediated the effect of turnover and motivation on village apparatus performance. The findings of this study confirm that improving village apparatus performance is not only determined by direct factors such as leadership, turnover, and motivation but is also significantly influenced by the level of work engagement of village apparatus.